GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 3168 species occurrences available in GBIF matching the query: TaxonKey: 5406285 HasCoordinate: true HasGeospatialIssue: false. The dataset includes 3168 records from 60 constituent datasets: 13 records from Herbarium Vonderau - FULD. 2 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 33 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 2 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from Tiroler Landesmuseum Ferdinandeum. 142 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 4 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 6 records from Estonian University of Life Sciences. 4 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 40 records from Colorado State University Herbarium. 1 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 4 records from The Flora of County Wexford. 74 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 14 records from Biodiversitätsdatenbank des Landes Salzburg. 2 records from Lund Botanical Museum (LD). 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 2 records from Consortium of California Herbaria. 280 records from Botanical Society of the British Isles - Vascular Plants Database. 6 records from IBF Monitoring of Vascular Plants. 6 records from Natural History Museum (London) Collection Specimens. 1 records from Universität Salzburg. 11 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 5 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 693 records from Observations du Conservatoire botanique national du Bassin parisien.. 8 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 2 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 1 records from Natural History Museum, University of Tartu. 4 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000. 4 records from Herbarium Senckenbergianum (FR). 2 records from BSBI tetrad data for Ireland. 3 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 13 records from Biological and palaeontological collection and observation data MNHNL. 1 records from Consortium of California Herbaria. 41 records from Dutch Vegetation Database (LVD). 45 records from Canadian Museum of Nature Herbarium. 25 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 2 records from Herbarium of The New York Botanical Garden. 39 records from Atlas des plantes vasculaires de Lorraine. 1 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 4 records from The Flora of County Wexford. 4 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 3 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 1522 records from FlorKart - FlorenKartierung Gefaesspflanzen. 16 records from Biologiezentrum Linz. 4 records from Flora-On: occurrence data of the flora of mainland Portugal. 6 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 1 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 3 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 3 records from Michigan State University Herbarium Vascular Plants. 2 records from The Flora of County Waterford. 11 records from Marie-Victorin Herbarium (MT). 1 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 2 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 30 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 3 records from Aranzadi Zientzi Elkartea. 1 records from Estonian Nature Observations Database. 6 records from inatura - Erlebnis Naturschau Dornbirn. 6 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens.
Keywords: GBIF; biodiversity; species occurrences